THE EFFECTIVENESS OF JIGSAW LEARNING STRATEGY TO IMPROVE STUDENTS’ READING ABILITY - Kurniawan Yudhi Nugroho; Khosiatul Fitri (Universitas Islam Sultan Agung, 2016)
This research was an attempt to investigate the use of Jigsaw learning Strategy in term of improving students’ reading ability. This six month project was conducted to Senior-high school students around Semarang. In order to get to know the impact of this program, this research required two classes designed as the class of experiment and the class of control. Each class would have its roles in this research. As the project was completely done, it was observed that the mean score of the posttest in the class ofexperiment (85.4412) was higher than that of the class of control (67.95). Of referring to the data, this was concluded that this learning strategy was positively effective to improve students’ learning performance in reading.